Calcium in crude oil: a review. (2nd December 2022) - Huo, Da; Wu, Jianxun; Li, Han; Huang, Haiyan; Chung, Keng H.; Shi, Quan
Abstract: Calcium in crude oil can cause equipment fouling and catalyst deactivation, hence the speciation of calcium in crude oil is of interest to the petroleum industry. This review summarizes various forms of calcium found in crude oils, includes inorganic calcium-containing compounds and organic calcium-containing compounds. The progress in characterization method and molecular composition of organic insoluble calcium-containing compounds are highlighted. The organic calcium compounds are mainly calcium naphthenate, therefore the challenge for the characterization of calcium compounds is the molecular characterization of the hydrolyzed naphthenic acids. With the advances in high-resolution mass spectrometry, the complex mixture of naphthenic acids can be characterized at the molecular level. Large molecular tetra carboxylic acids, which are derived from bacterial/eukaryotic lipids and/or archaeal membranes, are found the major component to form hard deposit with calcium ions. Naphthenic acids are considered as a key controlling factor for the calcium content in petroleum, however, the mechanism of interaction between calcium and naphthenic acid molecules is still not well understood.